Kuat Tekan Beton OPC Abu Terbang (Fly Ash) Di Air Gambut - Arnef Frenki; Alfian Kamaldi; Monita Olivia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study examines the mechanical properties of Ordinary Portland Cement (OPC) concrete and OPC concrete containing fly ash immersed in peat water. Fly ash as a pozzolanic material with high silica content is used as substitution of 25% of the volume of cement. The designed concrete strength was 21 MPa. Concrete Specimens was made in the cylinder mould with a diameter of 105 mm and height of 210 mm. The samples were first cured in fresh water for 28 days and then they were immersed in peat water for 7 and 28 days. The mechanical properties was evaluated by measuring the compressive strength of the concrete specimens. The total number of test specimens was 9 pieces, with 3 test specimens for each variation and testing age, which is without immersion, 7 and 28 days immersion in peat water. The pH value of peat water was ranging from 3.0 to 5.0. The result showed that the compressive strength of OPC concrete immersed in peat water decreased while the compressive strength of OPC concrete containing fly ash was dependent of how long the specimen was cured in peat water. The compressive strength of OPC-21 decreased by 7.08% at 28 days immersion in peat water while the compressive strength of OPC-FA-21 showed an increase of 8.81%.Keywords: Compressive strength, OPC, Fly Ash (FA), peat water